2013
DOI: 10.1093/jpepsy/jst002
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Adults With Type 1 Diabetes: A Comparison to Peers Without Diabetes

Abstract: Emerging adults with and without diabetes fare similarly on most dimensions studied during the first year out of high school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 45 publications
1
51
0
Order By: Relevance
“…In a previous report, we compared the two groups of emerging adults on psychological well-being and risk behaviors one year after high school graduation (49). In that report, we showed that the two groups did not differ in the life paths chosen (e.g., college), depressive symptoms, or disturbed eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, we compared the two groups of emerging adults on psychological well-being and risk behaviors one year after high school graduation (49). In that report, we showed that the two groups did not differ in the life paths chosen (e.g., college), depressive symptoms, or disturbed eating behavior.…”
Section: Discussionmentioning
confidence: 99%
“…When examining samples of young adults with type 1 diabetes only, Jacobson et al [26] found similar rates of high school graduation and post-high school education when comparing those with diabetes to a comparison group. Palladino et al compared the life courses pursued after high school by early young adults and also found that those with type 1 diabetes were equally likely to attend college as those without type 1 diabetes [27]. Thus, it appears that young adults pursue higher education at similar rates, but more nuanced research evaluating the day-to-day impact of type 1 diabetes management on attendance and achievement is needed.…”
Section: Young Adulthood and Lifestyle Considerationsmentioning
confidence: 99%
“…Diabetes status may influence decisions about timing and process of moving out of the family home; however, recent research suggests that diabetes does not influence living situation [27, 28]. Increasing young adults’ confidence in their abilities to manage diabetes and gradually shifting responsibility for diabetes management from family-based management to primarily individual management are important considerations when preparing for independent living situations [28, 29].…”
Section: Young Adulthood and Lifestyle Considerationsmentioning
confidence: 99%
“…Balfe and colleagues found that young adults with type 1 diabetes experienced distress regarding their daily management needs, stigma, and worry about their future [5]. In a study by Palladino et al [6], emerging adults with diabetes report lower level of life satisfaction and life purpose than peers living without type 1 diabetes. Management challenges are often complicated by developmental transitions of emerging adulthood such as attending college, obtaining employment, or living independently [7].…”
Section: Introductionmentioning
confidence: 99%